Lived Experiences of Patients with Chronic Kidney Disease Receiving Hemodialysis in Felege Hiwot Comprehensive Specialized Hospital, Northwest Ethiopia - Hailemariam Tadesse; Hordofa Gutema; Yosef Wasihun; Samuel Dagne; Yonatan Menber; Pammela Petrucka; Netsanet Fentahun (International Journal of Nephrology)
Purpose. Chronic kidney disease is a challenging disease and global public health problem. The burden of chronic kidney disease and hemodialysis is increasing in Ethiopia, but few studies explored the lived experiences of chronic kidney disease patients receiving hemodialysis. This study explored the lived experiences of chronic kidney disease patients receiving hemodialysis, in the Felege Hiwot Comprehensive Specialized Hospital, Bahir Dar City, Northwest Ethiopia, 2019. Methods. A phenomenological study design was conducted with 12 chronic kidney disease patients receiving hemodialysis between September 1 and October 30, 2019. A purposive sampling technique was used to select participants, and a semistructured in-depth interview guide was used to collect the data. The investigators audio-taped the interviews and then transcribed them verbatim. Finally, the transcribed data were imported to Atlas.ti™-7 software for coding, and then, thematic analysis was done. Transferability, dependability, credibility, and conformability were embedded to ensure data quality. Results. In this study, six major themes were emerged: (1) the seriousness of the disease, (2) challenges to get hemodialysis, (3) financial constraint, (4) restricted life, (5) feeling of dependency, and (6) psychological impacts. Conclusion. The restrictive nature of the disease affects a participant’s financial status which makes it challenging to obtain the service and increases feelings of dependency. These circumstances impact the psychology of the participants. We would recommend that every patient with hemodialysis needs social and psychological support. We would also recommend the need to extend the study to other areas of the country to confirm or disconfirm the findings.